Association between the religious coping of infertile people with their own quality of life and their spouses': A correlation study in iranian infertile couples - Tahmineh Dadkhahtehrani; Somayeh Momenyan; Saeide Heidari; Narges Momenyan (Wolters Kluwer Medknow Publications, 2018)
Background: Infertile couples have a lower quality of life (QoL) than that of the general population. Religious coping strategies (RCOPE) could affect QoL in distressing situations. The present study aimed to assess the association between the RCOPE of infertile people with their own QoL and that of their spouses'. Materials and Methods: This cross-sectional study was conducted among 200 infertile couples referring to Infertility Center of Qom, Iran in 2015. The data was collected using three questionnaires including Brief RCOPE scale, Short Form Health Survey, and a demographic questionnaire. p value of ≤0.05 was considered as significant level. Results: Multivariate analysis showed relationship between wives' RCOPE-N with their own QoL (β = −1.31, p < 0.001). Further, in husbands, RCOPE-P showed significant positive relationship with their own QoL (β = 0.80, p = 0.002), and their RCOPE-N had significant negative relationship with it (β = −0.61, p = 0.02). Surprisingly, wives' RCOPE-P showed negative relationship with husbands' QoL (β = −0.62, p = 0.04); whereas their RCOPE-N had no significant relationship with their husbands' QoL. In addition, neither RCOPE-P nor RCOPE-N of husbands had a significant relationship with their wives' QoL. Conclusions: In summary, we could not find an obvious and significant relationship between RCOPE of each spouse with QoL of the other spouse in infertile couples. Hence, further investigations with more participants of various religions are recommended.